An anesthetic management of negative pressure pulmonary edema - Dipti Raj; Kumari Priti; Hasina Quari; Rajesh Kumar Jha (Wolters Kluwer Medknow Publications, 2016)
Negative pressure pulmonary edema (NPPE) is one of the common complications of upper airway obstruction seen by anesthesiologist during either in induction or emergence sometimes both. Patients who have experienced NPPE are generally healthy without comorbidities. NPPE is a result of marked decrease in intrathoracic pressure caused by ventilator efforts against a closed glottis resulting in disruption of normal intravascular Starling mechanism, leading to transudation of intravascular protein, and fluids into the pulmonary interstitium. The onset of NPPE is usually rapid and without prompt recognition and intervention, the outcome can be fatal. This case report is of a 40-year-old female adult, who underwent right-sided percutaneous nephrolithotomy for stone in the right kidney otherwise uncomplicated surgical procedure.